From Catastrophism to Pessimism. Death and Sacrum in the Poetry of Stanisław Piętak - Wieliczko, Karolina Ewa (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
Stanisław Piętak’s poems are full of sadness and dark feelings. Poet was under the influence of theatmosphere of time between two world wars, which was reflected in Polish literature, especially as thecatastrophism. Fatalistic conception of human fate in his poetry rises from influence of Romanticism andDecadence, too. On the other hand, Piętak was eradicated from his folk heritage. Arcadia of childhoodseems irretrievably lost; that’s why poet was demonstrating nostalgia for death more and more. However,Piętak belonged to the informal poetry group around Józef Czechowicz, young poet was under the greatinfluence of his master’s works. In Piętak’s poems appeared obsession of death, typical for their literatureway of presentation of reality and revealing non-material sphere. Pietak’s poetry is searching of sacrumand absent God. His lyrics and poems are a testimony to premonition of his own death and the quasiapocalypticdestruction of the world and human culture. In the article we make an attempt to explainpoetic images of this prophecies with relation to the definition of catastrophism in Polish literature. Inthe text there are subjected to interpretation some representative poems, in which motifs relating to unrealitycould be found, for example: images of sky, symbolic representation of colours and flowers, guestsfrom the other world, etc. Piętak’s supplementary notes and commentaries were used to prove author’sspiritual condition over consecutive periods of his life and work. Analyses of selected poems from threelast volumes of poetry show an evolution of Piętak’s philosophy of literature.